2017
DOI: 10.1097/prs.0000000000003433
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Efficacy of Cryolipolysis on Saddlebags: A Prospective Study of 53 Patients

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Savacini et al observed similar results when cryolipolysis was used for esthetic flank contouring, 25 including a significant subcutaneous fat layer reduction, confirmed in further studies of the submental region (of 2.0 mm), the inner thighs (of 2.8 mm), the lateral thighs (of 2.6 mm), and the saddlebacks. 12,16,[25][26][27] Unfortunately, there is no comparative data available measuring the subcutaneous fat layer reduction after flap contouring by liposuction or partial excision.…”
Section: Discussionmentioning
confidence: 99%
“…Savacini et al observed similar results when cryolipolysis was used for esthetic flank contouring, 25 including a significant subcutaneous fat layer reduction, confirmed in further studies of the submental region (of 2.0 mm), the inner thighs (of 2.8 mm), the lateral thighs (of 2.6 mm), and the saddlebacks. 12,16,[25][26][27] Unfortunately, there is no comparative data available measuring the subcutaneous fat layer reduction after flap contouring by liposuction or partial excision.…”
Section: Discussionmentioning
confidence: 99%
“…The abdomen and flanks were the selected areas for treatment. According to one study, cryolipolysis has been shown to be effective in reducing localized subcutaneous fat from various anatomical areas, namely, the abdomen, flanks, arms, back, knees, and inner thighs 35 . However, Oliveira et al, state that although most studies reveal a significant reduction in fat in all areas evaluated, it is not yet known for sure which ones respond better to treatment, since this reduction may be dependent on factor, such as the vascularization and local cytoarchitecture as well as the metabolic activity of the adipose tissue deposits in question.…”
Section: Discussionmentioning
confidence: 99%
“…Coleman et al 25 used ultrasound to evaluate the fat layer thickness after cryolipolysis. Recently, Adjadj et al 27 used ultrasound to measure the decrease in fat thickness after cryolipolysis. Ultrasound imaging can quantitate changes in buttock thickness after fat transfer.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 This device has also been used to measure decreases in thickness after nonsurgical fat reduction including cryolipolysis. 25 27 Other novel applications include evaluation of facial hyaluronic acid injection and subcutaneous thickness after botulinum toxin injection. 28 30 …”
Section: Introductionmentioning
confidence: 99%